2019
DOI: 10.1039/c9fo00475k
|View full text |Cite
|
Sign up to set email alerts
|

Fermented carrot juice attenuates type 2 diabetes by mediating gut microbiota in rats

Abstract: Carrot juice fermented with Lactobacillus rhamnosus GG, enriched with free phenolics, organic acids and short-chain fatty acid, has the potential to ameliorate type 2 diabetes, in part through modulating specific gut microbiota and regulating the mRNA and protein expressions levels involved in glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 46 publications
3
41
0
1
Order By: Relevance
“…Ruminococcaceae have carbohydrate-active enzymes, sugar transport mechanisms, and metabolic pathways for the degradation of complex plant materials [41]. A reduction in Ruminococcaceae UCG-013 has been related to a disrupted carbon metabolism, which means body weight loss in chickens after E. tenella infection [42]. Romboutsia is a recently described bacterial genus that is usually associated with the health status of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcaceae have carbohydrate-active enzymes, sugar transport mechanisms, and metabolic pathways for the degradation of complex plant materials [41]. A reduction in Ruminococcaceae UCG-013 has been related to a disrupted carbon metabolism, which means body weight loss in chickens after E. tenella infection [42]. Romboutsia is a recently described bacterial genus that is usually associated with the health status of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, authors generally agree that fermentation significantly increases the levels of this class of bioactive compounds ( Table 1 ). Different raw materials have been studied, including milk [ 32 , 33 , 34 ], beer wort [ 35 ], fruit [ 36 ] and vegetables [ 2 ], and several bacteria strains have been used for fermentation.…”
Section: Increased Levels Of Scfas In Fermented Foods and Beveragementioning
confidence: 99%
“…Recently, a study reported a significant increase in SCFAs in L. rhamnosus GG -fermented carrot juice, compared with non-fermented ones (unfermented carrot juice: acetate 0.16 ± 0.02 mg/mL, propionate 0.51 ± 0.07 mg/mL, butyrate 0.64 ± 0.11 mg/mL; fermented carrot juice: acetate 0.42 ± 0.05 mg/mL, propionate 0.72 ± 0.09 mg/mL, butyrate 0.995 ± 0.09 mg/mL; p <0.05). Additionallyin this case, the fermentation of dietary fiber was considered as the main mechanism for the increased production of SCFAs [ 2 ].…”
Section: Increased Levels Of Scfas In Fermented Foods and Beveragementioning
confidence: 99%
See 1 more Smart Citation
“…According to the latest statistics, the incidence of asthma has been rising in recent decades, with the number of asthma patients increasing from 183 million in 1990 to 242 million in 2013. Infection by pathogenic microorganisms (especially viruses, chlamydia, mycoplasma, and mold) is one of the main causes of severe asthma [ 34 37 ]. For example, studies have shown that Proteus accounts for a higher proportion of microorganisms in asthma patients and that Firmicutes are reduced in asthma patients compared to normal people.…”
Section: Resultsmentioning
confidence: 99%